Fixed-dose combinations of enalapril and hydrochlorothiazide: effects on arterial hypertension treatment. GARANT Study, Part II - S. A. Shalnova; A. D. Deev (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To present the results of the GARANT study, Part II, supported by the Society of Cardiology of the Russian Federation. To study the effects of fixed-dose enalapril and hydrochlorothiazide combinations on arterial hypertension (AH) treatment in real(world clinical practice. Material and methods. The second part of the study included 3188 patients aged 18 years and above, with blood pressure (BP) level ≥160/95 mm Hg or isolated systolic AH, and without previous effective antihypertensive therapy. Mean age of the participants was >55 years, AH duration ~10 years; almost every subject was overweight or had high total cholesterol (TCH) level. More than 70% of the patients had left ventricular hypertrophy, every third suffered from heart disease, and 15,7% had stroke in anamnesis. Most of the patients (87,5%) received Enap HL 20 for 8 weeks. After 2 weeks of the treatment, 4,6% were switched to Enap Н, and 7,9% – to Enap НL. Results. The treatment was associated with systolic and diastolic BP (SBP, DBP) reduction as early as after the first two weeks: to 142,4±0,3 and 86,4±0,2 mm Hg, respectively. After 8 weeks, these parameters reached 134,5±0,2 and 82,4±0,1 mm Hg, respectively. Heart rate decreased by 5,0±0,1 bpm. After 8 weeks of the treatment, creatinine level did not change, and mean levels of glucose, TCH, uric acid, and potassium significantly reduced. Conclusion. After 8 weeks, treatment was effective in 53% of the participants. By the end of the study, SBP decrease by 20 mm Hg and DBP decrease by 10 mm Hg was observed in 86%. In total, 223 (6,9%) adverse events were registered. The results demonstrated metabolic neutrality of this antihypertensive combination.